2014
DOI: 10.1080/02188791.2014.960798
|View full text |Cite
|
Sign up to set email alerts
|

The demand for shadow education in China: mainstream teachers and power relations

Abstract: As in other parts of the world, private tutoring has expanded significantly in Mainland China during the past decade. This has been driven by factors including dramatic economic growth, high-stakes examinations, and the traditions of a Confucian culture at the macro-level, and school leadership and family incomes, at the micro-level. This paper examines the demand for private supplementary tutoring in Chongqing, China. It is based on a mixed-methods study of tutoring received by Grade 9 students. Based on an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 35 publications
2
53
0
1
Order By: Relevance
“…Previous research has already demonstrated the importance of understanding the social determinants and consequences of private tutoring (e.g., Zhang 2013; Zhang 2014; Xue, Wang, and Wu 2014). However, since these studies have all been based on regional data, we do not know whether their highly inconsistent results are generalizable (e.g., Lee, Kim, and Yoon 2004; Park and Lee 2005; Zhang 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has already demonstrated the importance of understanding the social determinants and consequences of private tutoring (e.g., Zhang 2013; Zhang 2014; Xue, Wang, and Wu 2014). However, since these studies have all been based on regional data, we do not know whether their highly inconsistent results are generalizable (e.g., Lee, Kim, and Yoon 2004; Park and Lee 2005; Zhang 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, it can improve the overall educational quality and the students' chances to succeed in their academic career (Stevenson & Baker, 1992;Bray, 1999;Baker et al, 2001;Suleman, Aslam, Hussain, & Ali, 2013) and improves students' self-efficacy (Montebon, 2016); but on the other, it may create many problems including corruption and malpractices (sometimes even coercion and blackmailing) by the teachers (Zhang, 2014), lack of interest in the mainstream school classes by both the students and the teachers who are involved in these activates (Mischo & Haag, 2002), financial pressure on the parents (Aslam, 2011), tax evasion (Silova, Budiene, & Bray, 2006), lack of time for the students for extracurricular activities (Bray, 2011), and various types of disparities it might cause amongst the students (Bray, 1999;Bray & Lykins, 2012). The issue of disparities caused by shadow education is often based on the argument that a certain group of students in the class has an advantage whereas the others do not.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, tutoring classes are a burgeoning business, and families with ambitions can hardly avoid them (W. Zhang, 2014). For the PISA survey (Programme for International Student Assessment) in 2012, seventy percent of Chinese students said they were taking additional math classes (OECD, 2013, p. 356), and the students participating in PISA 2015 spent twenty-seven hours a week with studying outside school, probably to a large extent at cram schools (OECD, 2016, p. 213).…”
Section: Escaping Cram Schoolsmentioning
confidence: 99%